2012
DOI: 10.1097/scs.0b013e31825757f9
|View full text |Cite
|
Sign up to set email alerts
|

Implant Handpiece With Adapted Drills in Orthognathic Surgery

Abstract: The attachment of bilateral sagittal-split osteotomy of the mandibular ramus with bicortical screws or the combination of miniplates and a bicortical screw is complicated through the intraoral approach because of the angle required for insertion of screws, so it is necessary to use a trocater. This article aimed to report a technique developed and used in 60 patients, wherein an implant handpiece with adapted drills was used in the intraoral attachment. The setting was performed intraorally to prevent scarring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…4,5 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 However, because of the esthetic disadvantage, some patients undergoing orthognathic surgery reject a transcutaneous approach. 15,21 To avoid skin incision, the authors performed intraoral bicortical screw fixation. Becker et al 15 reported that advantages of the intraoral approach include avoiding external skin scars and damage to the mandibular branch of the facial nerve, especially in patients requiring a high level of esthetic satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 However, because of the esthetic disadvantage, some patients undergoing orthognathic surgery reject a transcutaneous approach. 15,21 To avoid skin incision, the authors performed intraoral bicortical screw fixation. Becker et al 15 reported that advantages of the intraoral approach include avoiding external skin scars and damage to the mandibular branch of the facial nerve, especially in patients requiring a high level of esthetic satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…15,21 To avoid skin incision, the authors performed intraoral bicortical screw fixation. Becker et al 15 reported that advantages of the intraoral approach include avoiding external skin scars and damage to the mandibular branch of the facial nerve, especially in patients requiring a high level of esthetic satisfaction. Many surgeons have preferred to use bicortical screw fixation systems, and the use of miniplates with monocortical screws is less frequent in BSSO setback surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another complicating factor in fixation is the angle required for accurate screw placement, particularly when locking plates and an intraoral approach are used. The use of an implant handpiece with adapted drills consistent with the technique described by this team is vital for overcoming restrictions that limit access for screw insertion into the mandibular angle and ramus. This type of handpiece facilitates drilling and screw insertion without requiring an extraoral approach, ensuring that the entire surgical procedure can be conducted via intraoral access.…”
Section: Discussionmentioning
confidence: 99%
“…The previously adapted plate is definitively adjusted along the bone edge during the surgical procedure (see Figure ). Drilling and screw insertion for fixation are performed using an implant handpiece with adapted drills (see Figure ), as previously described in the literature, adhering to accepted guidelines specifying a maximum angle of 20° for the locking plates. A 1.6‐ × 17‐mm bur is used at 2000 rpm in the implant handpiece (20:1) for bicortical drilling.…”
Section: Introductionmentioning
confidence: 99%